Parental line selection for yield contributing character of rice (Oryza sativa) - Bhuiyan, MSH; Malek, MA; Ikbal, MF; Topu, A; Alam, ABMS (International Journal of Agricultural Research, Innovation and Technology, 2017)
The prime objective of any hybrid program is to bring the desirable genes present in the parent into a single genetic background. Therefore, an experiment was conducted to evaluate the parental performance at the experimental farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University. Nine A (male sterile) lines and Four R (restoral) lines were used here. To consider their performance various agronomic trait was selected and most emphasis was provide for plant height, days to maturity and other yield contributing character. The characters studied in this investigation exhibited low to moderate range of variability and heritability. Out of all RGBU0014A perform the height days to maturity then others. Although yield is more or less similar for the restorer parent, but considering other agronomic yield contributing trait RGBU003A, RGBU002A, RGBU009A can be selected to cross with superior restoral SL8 R and Mitali R to obtain ideal plant type. Int. J. Agril. Res. Innov. & Tech. 7 (1): 46-50, June, 2017